Pengaruh Capital, Asset Quality, Management, Earnings, Dan Liquidity terhadap Pertumbuhan Laba pada Perusahaan Perbankan Umum Terdaftar di BEI - Sitana Salwa Zulaicha; Fajar Syaiful Akbar (Al-Buhuts, 2025)
This study aims to examine the effect of factors within the CAMEL framework (Capital, Asset Quality, Management, Earnings, and Liquidity) on banking profit growth. This research is motivated by the inconsistency of prior empirical findings regarding the determinants of banking financial performance, particularly in the context of post-pandemic economic dynamics. The study employs a quantitative approach using secondary data obtained from the financial statements of banking companies listed on the Indonesia Stock Exchange over the period 2020–2022. The sample was selected using a purposive sampling technique, resulting in 30 companies. Data analysis was conducted using multiple linear regression. The results indicate that capital and liquidity have a significant effect on profit growth, while asset quality, management, and earnings do not exhibit significant effects. These findings suggest that capital strength and liquidity capability are key determinants in driving banking profit growth, particularly under conditions of economic uncertainty. This study provides empirical contributions to the literature by reinforcing the effectiveness of the CAMEL framework in predicting banking financial performance in Indonesia.